Comparison of the 3D Protein Structure Prediction Algorithms - Al-Akwaa, Fadhl M.; Elhetari, Husam; Al Naggar, Noman; Al-Rumaima, Mahmoud A. (International Journal of Engineering Research and Applications, 2014)
Determining protein 3D structure is important to known protein functions. Protein structure could be determined experimentally and computationally. Experimental methods are expensive and time consuming whereas computational methods are the alternative solution. From the other hand, computational methods require strong computing power, assumed models and effective algorithms. In this paper we compare the performance of these algorithms. We find that Genetic Algorithm with improved search techniques can represents the best heuristic algorithm to predict 3D protein structure from AB off or HP lattice model.